Development of a Data Curatorship and Management module at a CODeL higher education institution. Issue 1 (1st December 2022) - Mojapelo, Makutla; Jacobs, Lorette; Marutha, Ngoako
Abstract : As a developing subdiscipline within the context of archives and records management, data curatorship and management focuses on maintaining, preserving and adding value to digital research data throughout its lifecycle. Though data curatorship and management have been implemented within archives and records management programs in industrialized countries, the training of archivists and records managers in the principles and application of data curation in Africa has not received the same attention. To rectify this, the International Council on Archives (ICA) proposed a generic curriculum for modules with the focus on data curatorship. Linked to these guidelines, this article addresses the development of a data curatorship and management module within a Comprehensive Open Distance eLearning (CODeL) University. The research relied on the views and experiences that the authors obtained during the design phase, contextualized within an interpretivism paradigm. Policies, existing literature and guidelines proposed by the ICA informed the scope and context of the information included within the module. Aligned to the principles of the bricolage design, the ADDIE model and responsive curriculum theory was applied to provide a framework for the development of the data curatorship and management module at the CODeL institution. Findings revealed that developing a data curatorship and management module for the African context entails the consideration of many factors to ensure that students are prepared for applying new knowledge within changing workplace environments.